The permanently shadowed regions of dwarf planet Ceres. Issue 13 (6th July 2016) - Schorghofer, Norbert; Mazarico, Erwan; Platz, Thomas; Preusker, Frank; Schröder, Stefan E.; Raymond, Carol A.; Russell, Christopher T.
Abstract: Ceres has only a small spin axis tilt (4°), and craters near its rotational poles can experience permanent shadow and trap volatiles, as is the case on Mercury and on Earth's Moon. Topography derived from stereo imaging by the Dawn spacecraft is used to calculate direct solar irradiance that defines the extent of the permanently shadowed regions (PSRs). In the northern polar region, PSRs cover ∼1800 km 2 or 0.13% of the hemisphere, and most of the PSRs are cold enough to trap water ice over geological time periods. Based on modeling of the water exosphere, water molecules seasonally reside around the winter pole and ultimately an estimated 0.14% of molecules get trapped. Even for the lowest estimates of the amount of available water, this predicts accumulation rates in excess of loss rates, and hence, there should be fresh ice deposits in the cold traps. Key Points: Permanently shadowed regions (PSRs) identified in the north polar region of Ceres Northern PSR area is about 1800 km 2 based on topography‐derived illumination model According to exosphere model calculations, fresh ice deposits are expected in the cold traps